Grasping the nettle and enduring the pain: healthcare priority setting and disinvestment in the context of prudent healthcare - Pippa Anderson (2017)
Since the financial crisis of 2008 economic pressures mean that healthcare budgets were and still are substantially constrained. The NHS in Wales has had to face the reality of rationing healthcare. Implementation of fair and equitable rationing is a challenge, however. This is a situation where the economic concepts of scarcity, opportunity cost and the margin can support effective prioritisation and resource reallocation decisions. In this context, the aim of this research was to develop pragmatic prioritisation and resource reallocation frameworks for the Welsh Health Specialised Services Committee (WHSSC) who commission highly specialised technologies for Wales and commissioning boards in Abertawe Bro Morgannwg University Health Board (ABMUHB). The prioritisation and resource reallocation methods for WHSSC were developed over a series of prioritisation meetings resulting in a framework based on based on multi-criteria decision analysis methods. In ABMUHB, programme budgeting marginal analysis (PBMA) was the approach used and two pilot PBMAs run in different service areas. Disinvestment and ‘doing less’ to invest in more beneficial activities within budget were accomplished in one pilot project; the other project managed resource reallocation but revealed issues in achieving service standards. Both pilots enabled development of a PBMA Framework for ABMUHB. Group decision support methods were an important feature of implementation of decision making in all three projects. The research conducted for this thesis has shown it has been possible to develop and deliver robust, evidence based, effective and practical frameworks based on economic concepts for prioritisation, disinvestment and resource reallocation. Both organisations have taken ‘ownership’ of the frameworks and will make them a ‘way of working’ for the future rather than an academic exercise. A key learning of the research was that pragmatism must prevail if prioritisation and resource reallocation methods are to gain traction and become embedded in commissioning.